PHYSICO-CHEMICAL ASSESSMENT OF SURFACE AND GROUNDWATER QUALITY IN SAVANNAH SUGAR COMPANY, NUMAN AND ITS ENVIRONS, ADAMAWA STATE, NIGERIA - Ijantiku, Joseph; Mohammed, Abdulaziz; Lukas, Martin; Seli, Ahmed Buba (FUDMA JOURNAL OF SCIENCES, 2025)
This research is aimed at evaluating surface and groundwater quality around the Savannah Sugar Company, Numan, and its environs. The analysis indicated that total hardness ranged from 43.9-91.0 mg/L and DO ranged from 4.2-11.3 mg/L, BOD ranged from 6.6-116.0 mg/L, and COD 10.4-139 mg/L, while Nitrate varied from 4.1-80.1 mg/L. Spatial analysis indicated a significant concentration of nitrate and iron at the northwestern flank of the study area. pH varied from 5.3 to 9.2, Electric conductivity (EC) 178-605 µS/cm; TDS ranged from 115-401 mg/L. Fe, Cu, Mn, Zn were below WHO/FMEnv limits, with iron (Fe) reflecting an average of 0.3 mg/L; while others were <0.1 mg/L, except for localized high concentrations of iron and nitrate. For the surface water samples, the following results represent the quantitative values of the physico-chemical parameters analyzed: pH ranged from 5.3 to 9.4, EC ranged from 181-773 µS/cm, while TDS ranged from 122-512 mg/L. The cation Na+, K+, Ca2+, Mg2+ and anion HCO3-, Cl-, SO42-, ranged from 40.2-98.7 mg/L, DO 4.0-11.1 mg/L, BOD 28.1-98.5 mg/L, and COD 41.0-141.3 mg/L. Nitrate ranged from 38.4 to 84.9 mg/L. Fe, Cu, Pb, Mn, Zn, and F were significantly below WHO/FMEnv limits; iron (Fe) varied from 0.1-5.6 mg/L. However, high Fe and nitrate were also observed in the northwestern part of the study area. Generally, the surface and groundwater quality fall within the WHO/FMEnv permissible limit for drinking water.